Free Vibration Analysis of Sandwich Plate-Reinforced Foam Core Adopting Micro Aluminum Powder - Al-Waily, Muhannad; Raad, Hussam; Njim, Emad Kadum (Physics and Chemistry of Solid State, 2022)
Analytical study of free vibration behavior of foam core sandwich plates strengthened with Aluminum micro spherical powder were presented in this paper. Sandwich plate with polyurethane foam core sandwiched between two Aluminum faces. To calculate the natural frequencies, use Kirchhoff theory to drive the equation of sandwich plate vibration. The stiffness characteristics of a foam-Aluminum core were evaluated by micro particle composite equations. The findings reveal that the impact of filling foam is effective, according to the free vibration analysis, the sandwich plate's free vibration and static behavior can be improved by using micro spherical powder foam in the vacant spherical gaps of the foam core. In comparison to other cores, the core foam-aluminum sandwich plate deflects less.